Proses Pengolahan Air Minum pada Sumber Karangan Perumda Air Minum Tugu Tirta Kota Malang - Erna Maya Safa; Lilis Sulistyorini (Universitas Airlangga, 2024)
Background: Water is needed by humans, especially drinking water. Drinking water can be directly consumed if it meets the requirements in PERMENKES No.492/2010 concerning Drinking Water Quality Requirements. Sumber Karangan is the raw water source for PDAM Kota Malang has met the requirements for drinking water quality. Sumber Karangan raw water only uses a partial processing method, namely by using chlorination. Objectives: In general, this study aims to explain the drinking water treatment process at Sumber Karangan. In particular, this study aims to determine the results of drinking water treatment by looking at the quality of drinking water physically, chemically, and bacteriologically at Sumber Karangan. Methods: This study uses exploratory research methods through qualitative data collection by conducting interviews, direct observation, and literature review as supporting information related to drinking water treatment processes. Results: Based on what we got on the field, the steps taken are intake, chlorination, reservoir, flushing, and customer distribution. Examination of the quality of raw water shows that the quality of raw water at Sumber Karangan only requires chlorination as a disinfection process. While checking the quality of the customer's drinking water shows that the quality meets the requirements in PERMENKES No.492/2010 concerning Drinking Water Quality Requirements. Conclusions: The drinking water treatment process at Sumber Karangan is following applicable regulations and has been distributed to customer networks with guaranteed safety so that it can be consumed directly by customers.